Color characteristics and psychological healing effects in Rokuon-ji Temple Garden: a quantitative analysis - Wang, Jinyang; Kunii, Yoichi (Frontiers in Psychology, 2025)
This study quantitatively analyzed the color characteristics and psychological healing effects of Rokuon-ji Temple Garden (Kinkaku-ji) through a systematic methodology combining color extraction, fractal analysis, and semantic differential evaluation. From an initial collection of 150 photographs documenting the garden’s complete visitor experience, 42 landscape photographs were systematically selected based on healing quality ratings (mean ≥5.0, median ≥5.0, standard deviation <1.2) and analyzed for six color categories (red, yellow, brown, gray, white, green) using three quantitative metrics: fractal dimension, diversity index, and concentration index. Factor analysis of semantic differential evaluations from 58 participants identified six psychological dimensions: Openness, Decorativeness, Clarity, Naturalness, Unity, and Complexity. Hierarchical cluster analysis revealed eight distinct landscape types with characteristic color profiles corresponding to specific psychological effects. Significant correlations were found between color metrics and psychological factors, particularly between brown fractal dimension and Openness (r = 0.455), green fractal dimension and Naturalness (r = 0.402), and white concentration and Unity (r = 0.350). The findings provide evidence-based guidelines for therapeutic garden design while demonstrating that the healing efficacy of traditional Japanese gardens derives from sophisticated orchestration of color complexity, diversity, and concentration patterns.